Tenure. Bibliographies in Education No. 33 - Canadian Teachers' Federation, Ottawa (Ontario).; Canadian Teachers' Federation, Ottawa (Ontario). ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This bibliography contains 286 reference works on tenure completed within the last 10 years. The bibliography contains books, articles and excerpts from books, and theses. The titles which have a single asterisk show availability through the Canadian Teacher's Federation Library. Titles with a double asterisk indicate availability in microform only. Titles followed by an ED number indicate the availability of abstracts in "Research in Education". The titles followed by "Available in ERIC" indicate that the purchase of hard or microfiche copies is possible through the ERIC Document Reproduction Service. The complete listing of the Bibliographies in Education series is included. (BRB)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Freedom; Contract Salaries; Contracts; Probationary Period; Teacher Employment; Teacher Welfare; Tenure